DISTANT EDUCATION DURING COVID-19 LOCKDOWN: A MOROCCAN OFFICIAL REPORT’S REVIEW - Youssef Laaraj (International Journal of Scientific Research and Innovative Studies, 2024)
Traditionally confined to physical classrooms, formal education underwent a rapid transformation as Information and Communication Technologies (ICTs) became integral to teaching and learning processes worldwide. However, the extent of ICT integration varied widely across regions prior to the pandemic, with many areas experiencing limited technological adoption. The sudden closure of schools in March 2020 precipitated an urgent shift to online education, presenting unprecedented challenges for students, parents, and educators. Over the subsequent two academic years (2019-2020 and 2020-2021), Morocco grappled with fluctuating between online and face-to-face learning modalities, profoundly altering educational dynamics and impacting learning outcomes. The CSEFRS report critically assesses the success and challenges of this transition, employing a blend of statistical data and qualitative insights from questionnaires and interviews with teachers and students. This is a comprehensive analysis and review of the implementation and outcomes of distance education during the COVID-19 lockdown in Morocco, relying on the official report by the Higher Council of Education, Training, and Scientific Research (CSEFRS). This analysis not only evaluates the practicality and efficacy of distance education during crisis situation but also informs future educational policies and practices in Morocco and beyond, offering valuable insights for global educational resilience strategies Key words: Morocco, Distant education, ICT integration, E-learning effectiveness. Received Date: June 20, 2024 Accepted Date: July 20, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/173 DOI: https://doi.org/10.5281/zenodo.13146991